Ablation of left posterior fascicular tachycardia during sinus rhythm under the guide of non-contact array. (12th October 2011) - Jian, Xu; Xianlin, Sun; Hao, Su; Ming, Cheng; Hongjun, Zhu; Chunsheng, An; Fuyuan, Liu; Xizheng, Fan; Ji, Yan
Abstract : Aims: To explore the effectiveness and safety of catheter ablation for left posterior fascicular ventricular tachycardia under the guide of Ensite3000/array. Methods: Patients with left posterior fascicular ventricular tachycardia from March 2009 to March 2011 in our centre were studied, including 1 perinatal cardiomyopathy patient and 2 dilated cardiomyopathy patients. Three dimensional geometry were constructed using Ensite3000/array and His bundle, left bundle branch, left posterior fascile and sinus rhythm breakout point were marked during sinus rhythm. The P potential and diastolic potential were mapped using array rapidly in the area just above sinus rhythm breakout point and after confirmation by ablation catheter, a patchy ablation method were used with the appearance of left posterior fascicular block in ECG and no further ventricular tachycardia induction as a end point of ablation. Results: The duration of VT QRS complex was 125.6±10.2 ms with RR interval 356.5±38.6 ms. The P potential and diastolic potential were all successfully mapped and 24 patients developed left posterior fascicular block in ECG and all patients having no further ventricular tachycardia induced. During follow-up, 1 patient had recurrent ventricular tachycardia and second ablation was performed resulting in deeper q wave in lead II, III and aVF and no ventricular arrhythmia induction. Conclusion: Under the guide of Ensite3000/array, after marking of left posterior fascicle and mapping of P potential and diastolic potential as target, patchy ablation in the area between sinus breakout point and His bundle with appearance of left posterior bundle block and no VT induction as an end point might cure left posterior fascicular ventricular tachycardia rapidly, effectively and safely.